Z = 1 - 1 + 1 - 1 + 1..... Z' =0 +1 - 1 +1 - 1.....

Z+Z' => All but the 1st term cancel out, leaving just 1. 2Z = 1. Z = 0.5

Or another way:

Z = 1 - 1 + 1 - 1 + 1..... Z = 1 - 1 + 1 - 1 + 1.....

2Z = 2 - 2 + 2 - 2 + 2..... So, 2Z is either 2 or 0; average 1. 2Z = 1. Z = 0.5

## You're correct, the author's formation of Z+Z appears incorrect.

Z = 1 - 1 + 1 - 1 + 1.....

Z' =0 +1 - 1 +1 - 1.....

Z+Z' => All but the 1st term cancel out, leaving just 1.

2Z = 1.

Z = 0.5

Or another way:

Z = 1 - 1 + 1 - 1 + 1.....

Z = 1 - 1 + 1 - 1 + 1.....

2Z = 2 - 2 + 2 - 2 + 2.....

So, 2Z is either 2 or 0; average 1.

2Z = 1.

Z = 0.5